2019
DOI: 10.1515/chem-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Jatropha seed oil derived poly(esteramide-urethane)/ fumed silica nanocomposite coatings for corrosion protection

Abstract: Jatropha oil [JO] based poly (esteramide-urethane) coatings embedded with fumed silica nanoparticles were prepared. JO was converted to N,N-bis(2-hydroxy ethyl) JO fatty amide (HEJA) and was further modified by a tetrafunctional carboxylic acid(trans 1,2 diaminocyclo-hexane-N,N,N’,N’,-tetraacetic acid) to form poly (diamino cyclohexane esteramide) (PDCEA). PDCEA was then treated with toluene 2,4-diisocynate and fumed silica to prepare poly(diamino cyclohexane urethane esteramide) (PUDCEA) nanocomposite. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Alam et al designed an anticorrosive PEsA polyol by replacing typical dicarboxylic acids with EDTA [ 62 ], ethylene glycol tetraacetic acid [ 124 ], and itaconic acid/ trans -1,2-diaminocyclohexane-N,N,N′,N′,-tetraacetic acid [ 46 , 154 ], employing LO, PO, and JO, respectively. The PU coatings prepared from EDTA and trans -1,2-diaminocyclohexane-N,N,N′,N′-tetraacetic acid-based polyols have a combination of amine groups, ester groups, urethane groups, and pendant alkyl chains.…”
Section: Nonedible Vegetable Oil-based Polyurethane Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alam et al designed an anticorrosive PEsA polyol by replacing typical dicarboxylic acids with EDTA [ 62 ], ethylene glycol tetraacetic acid [ 124 ], and itaconic acid/ trans -1,2-diaminocyclohexane-N,N,N′,N′,-tetraacetic acid [ 46 , 154 ], employing LO, PO, and JO, respectively. The PU coatings prepared from EDTA and trans -1,2-diaminocyclohexane-N,N,N′,N′-tetraacetic acid-based polyols have a combination of amine groups, ester groups, urethane groups, and pendant alkyl chains.…”
Section: Nonedible Vegetable Oil-based Polyurethane Coatingsmentioning
confidence: 99%
“…The PU coatings prepared from EDTA and trans -1,2-diaminocyclohexane-N,N,N′,N′-tetraacetic acid-based polyols have a combination of amine groups, ester groups, urethane groups, and pendant alkyl chains. JO-derived poly(esteramide urethane)/fumed silica nanocomposite PU coatings were demonstrated by Alam et al, which showed good adhesion, hardness, gloss, and anticorrosive properties [ 154 ]. NO-based PEsA polyols were also prepared for self-healing anticorrosive PU coatings, where polyamidoamine-based polyurea microcapsules were filled with LO [ 28 ].…”
Section: Nonedible Vegetable Oil-based Polyurethane Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has also shown intermediate inhibition against further gram negative bacteria (P.aeruginosa) (Khane et al , 2016). Poly (ester-amide urethane) coatings based on Jatropha oil embedded with fumed silica nano-particles, have been prepared and the physico-mechanical and corrosion resistance results indicated that the modified nano-composite coatings showed the desirable properties of a mild steel substrate (Alam et al , 2019). Vegetable oil-based poly (ester-amide)s are essentially amide modified alkyds, which show improved coating film properties when compared alongside normal alkyds.…”
Section: Introductionmentioning
confidence: 99%